METODE UJI USECASE TERHADAP FLOWCHART PROSES APLIKASI DATA SOSIAL REKAM MEDIS WARGA RT.06 RW.02 KELURAHAN TUNJUNGSEKAR KOTA MALANG - Djuwadi, Ganif; Trisnanto, Puguh Yudho; Prabowo, Yudhi; Khairuddin, Khairuddin; Pitoyo, Zani; Rahman, Zainol (DINAMIKA DOTCOM, 2019)
Usecase Test Method on Flowchart Process Application of Social Data Record Medical Citizens RT.06 RW.02 Village Tunjungsekar Malang. System running is basically a system that has a system component that must be done to know the functionality of interrelationship with other systems. Social data Citizen Record RT.02 RW.06 has a GCS function with a basic assessment so as to produce a running system that has a data transfer transport with GCS value = 5 has high system dependency, the boundry section of th system has usecase Assocations with GCS = 3 average the running system has the ability of the system usesblity received by the user user in the form of data storage citizens into the database. So that the performance of the system in the form of social data input interface Medical Record RT.06 residents RW.02 Tunjungsekar urban village when implemented produce usecase interaction with flowchart process produce GCS = 2 moderate system. Keywords : General characteristics of system, Social record medical data, Data movement